ANALISIS RANTAI PASOK (SUPPLY CHAIN) KOMODITI KEDELAI PADA PENGUSAHA TEMPE DI KECAMATAN BELITANG MULYA KABUPATEN OKU TIMUR (JASEP, 2018)
This study aims to analyze Supply Chain of Soybean Commodity at Tempe Entrepreneurs in Belitang Mulya Sub-district, OKU Timur District, to analyze the total marketing margin obtained by small soybean entrepreneurs and tempe entrepreneurs in Belitang Mulya Sub-district of OKU Timur Regency, and to analyze the added value of soybean commodity which is obtained by tempe entrepreneurs in Belitang Mulya sub-district, OKU Timur Regency using marketing margin and hayami method, this research is done from March until July 2017.The location determination was done purposively with the consideration of location taken by the majority of tempe entrepreneurs in Belitang Mulya Sub-district, East Ogan Komering Ulu Regency. The research method used in this research is survey method and sampling method used is multistage random sampling that amounted to 19 tempe entrepreneurs who were sampled with a total of 37 tempe entrepreneurs.The results showed that the perpetrators of the supply chain of soybean commodity in tempe entrepreneurs in Belitang Mulya sub-district of OKU Timur Regency consisted of overseas soybean farmers, large soybean traders (importers), small soy swords, tempe and consumer entrepreneurs. Where the flow of products flowing from soybean farmers abroad to the tempe entrepreneurs who then immediately sold to consumers in the form of tempe. Soybean marketing channel conducted by small soy traders named Agus Budiono is the most efficient soybean marketing because it has the lowest functional cost among other small soybean traders in District Belitang Mulya Regency OKU East that is Rp.62,5 per Kg soybean with a total margin of Rp.600 per Kg of soybeans. Meanwhile, tempe marketing by tempe entrepreneurs named Sofia is the most efficient tempe marketing because it has the lowest functional cost among other tempe entrepreneurs in Belitang Mulya sub-district of East OKU Regency which is Rp.1.160 per Kg of soybean with total margin equal to Rp.8.300 per Kg of soybeans. In the supply chain of soybean commodity to tempe entrepreneurs in Belitang Mulya Sub-district, OKU Timur Regency, tempe entrepreneurs get the added value of Rp. 303406.